Midnight Sun - view from hotel on Franklin Avenue, Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
This photograph was taken at 12:34 a.m. on July 8, 2015. At that hour, sunlight is reflected off the tilted windows of the building in the foreground and also from some of the background buildings. ...